1992
DOI: 10.1080/03670244.1992.9991224
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on food cravings and aversions during pregnancy

Abstract: The effects of cultural choices on food cravings and aversions of 160 pregnant women were assessed in four ethnic groups (n = 40 each): Black, Cambodian, Hispanic and White. Subjects were participants in a federal supplemental food program, the Women, Infants and Children Program (WIC), in Long Beach, California, a metropolitan area of the United States. Questionnaires were administered in Cambodian, English, or Spanish as appropriate. Cambodians craved significantly more meat and spicy/salty foods than the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…This would imply that women who avoid foods are better off economically and nutritionally. Another possible explanation based on the results of this study is that the correlation of food aversion with food craving (which was also observed by Coronios-Vargas et al [2] and Alemu and Wolde-Gabreil [personal communication, 1995]) might account for the better nutritional status of those women who avoided specific foods.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…This would imply that women who avoid foods are better off economically and nutritionally. Another possible explanation based on the results of this study is that the correlation of food aversion with food craving (which was also observed by Coronios-Vargas et al [2] and Alemu and Wolde-Gabreil [personal communication, 1995]) might account for the better nutritional status of those women who avoided specific foods.…”
Section: Discussionmentioning
confidence: 60%
“…The high prevalence of aversion to cereal foods (which are the most commonly consumed foods in the area) supports the widely held view that pregnant women avoid staple foods. Coronios-Vargas et al [2], in an extensive study that covered four ethnic groups in the United States, observed that women avoided staple foods. Similar results were reported in a study in Ethiopia [F. Alemu and Z. Wolde-Gabreil, personal communication, 1995].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations